SR-groups of Order 2npm with Dihedral Sylow 2-subgroup - V. V. Yanishevskiy (Моделирование и анализ информационных систем)
The structure of SR-groups with dihedral Sylow 2-subgroup modulo Frattini subgroup is described. It is proved that if a group О is a non-supersolvable SR-group of order 2npm with dihedral Sylow 2-subgroup, p is Mersenne prime.